TOWARD CLIMATE-RESILIENT FORESTRY POLICIES: EVIDENCE-BASED POLICY ANALYSIS IN INDONESIA - Mendes, Clara; Costa, Bruna; Alves, Livia (Journal of Selvicoltura Asean, 2026)
Indonesia’s tropical forests face increasing threats from climate change, deforestation, and unsustainable land use, creating urgency for adaptive and resilient forestry policies. Existing regulations often lack integration of empirical evidence and climate risk considerations, resulting in suboptimal governance outcomes. Understanding the effectiveness of policy interventions is critical for enhancing forest resilience and mitigating environmental and socio-economic impacts. This study aims to evaluate the effectiveness of Indonesia’s forestry policies through an evidence-based lens, emphasizing climate resilience, legal frameworks, and participatory governance. The research investigates how policy design and implementation align with environmental, social, and technological factors that influence forest sustainability. A mixed-methods approach was employed, combining quantitative analysis of deforestation rates, forest cover data, and climate vulnerability indicators with qualitative assessments from policy document reviews, stakeholder interviews, and expert consultations. Triangulation of data sources provided a robust evaluation of policy outcomes and implementation challenges. Results indicate that policies incorporating climate adaptation strategies, technological monitoring, and participatory mechanisms achieve higher effectiveness in sustaining forest cover and reducing illegal activities. Gaps remain in enforcement, institutional coordination, and local stakeholder engagement, highlighting areas for improvement. Evidence supports the integration of adaptive, evidence-based, and participatory approaches into national forestry policies to enhance climate resilience and sustainable forest management. Findings provide actionable guidance for policymakers, practitioners, and international partners in tropical forest governance.